Method for preparing SnS / TiO2 film at low temperature and application of SnS / TiO2 film in PEC type self-powered optical detection
The SnS film was grown by low-temperature chemical bath deposition method on TiO2 film to form a SnS/TiO2 heterojunction film, which solved the problem of limited photoresponse range and fast carrier recombination of TiO2 photoanode material, achieved efficient photocurrent density and fast response time, and widened the photoresponse range to the visible region.
Patent Information
- Application Number
- CN202311274773.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The existing TiO2 photoanode materials have light response in the ultraviolet region, but the light response range is limited and the photogenerated carrier recombination is fast, making it difficult to effectively improve the problems of insufficient light absorption and serious carrier recombination.
SnS films were grown in situ on TiO2 film by low-temperature chemical bath deposition method to form SnS/TiO2 heterojunction films, widening the light response range and improving the light absorption efficiency.
It has achieved a 9-fold increase in photocurrent density under ultraviolet light, shortened the response time to 40ms, and widened the light response range to the visible region, and is suitable for dual-wavelength (UV-Visible) optical communication applications.
Smart Images

Figure CN119715680A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optical detection, and in particular relates to a method for preparing SnS / TiO2 thin film at low temperature and its application in PEC type self-powered optical detection. Background Art
[0002] Photoelectrochemical (PEC) photodetectors have simple manufacturing processes and low production costs, and have great application prospects in the field of optoelectronic devices. Based on the structural advantages of PEC photodetectors, directional separation and transfer of photogenerated carriers can be achieved, which is conducive to the construction of self-powered photodetection devices. In order to obtain high-performance PEC photodetectors, the photoanode material needs to have good light absorption characteristics and a large specific surface area, and due to the participation of electrolytes in the working process, the photoanode material needs to have good chemical stability. Titanium dioxide (TiO2) is widely used in ultraviolet light detection research due to its stable physical and chemical properties, suitable bandgap width and easy synthesis. The physical synthesis methods of TiO2 include magnetron sputtering and physical vapor deposition, and the chemical growth methods include chemical vapor deposition, liquid deposition, sol-gel and spin coating. Usually, the preparation of high-quality and high-crystallinity TiO2 films requires high-energy electromagnetic fields or high-temperature calcination treatment, which limits the selection of conductive substrates. Among them, the liquid deposition method does not require high temperature, high pressure or high vacuum conditions, and the preparation process is simple and safe. Under low temperature conditions, batch production of crystalline TiO2 films can be achieved on different substrates.
[0003] TiO2 semiconductor materials with wide band gap (Eg = 3.2eV) only have light response in the ultraviolet region, which limits the response range to light, and the photogenerated carriers recombine quickly. In order to solve this problem, single TiO2 can be morphologically regulated, doped, or compounded with other narrow band gap semiconductor materials (SnS, CdS, CuInS, etc.) to improve the carrier separation efficiency, transmission path and light response range. However, morphological regulation and doping are difficult to fundamentally improve the problems of insufficient light absorption and serious carrier recombination of TiO2. Introducing semiconductor materials with a wide spectral absorption range and a large light absorption coefficient to construct a type II heterojunction with TiO2 is conducive to promoting the separation of carriers and broadening the light response range of the device. SnS has an optical band gap of 2.12eV, a high light absorption coefficient with good visible light response, and a simple preparation method. By low-temperature chemical bath deposition, SnS thin film can be in-situ grown on TiO2 thin film to obtain SnS / TiO2 visible light responsive photoanode film. Researchers have used different synthesis methods to obtain SnS / TiO2 heterojunction films and applied them to fields such as solid-state photodetectors and solar cells, but there is little research on PEC-type photodetectors. The method of preparing heterojunction films at low temperatures provides the possibility of preparing flexible photodetectors and can be applied to fields such as optical communications, wearable devices, healthcare, security and environmental monitoring. Summary of the invention
[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a SnS / TiO2 thin film.
[0005] Another object of the present invention is to provide a method for preparing the above SnS / TiO2 film.
[0006] Another object of the present invention is to provide an application of the above SnS / TiO2 film in PEC type self-powered light detection.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A SnS / TiO2 film comprises a TiO2 film and a SnS film covering the TiO2 film, wherein the TiO2 film is composed of granular TiO2 and the SnS film is composed of stacked flaky SnS particles.
[0009] A method for preparing a SnS / TiO2 thin film comprises the following steps:
[0010] S1, mixing a boric acid aqueous solution and an ammonium fluorotitanate aqueous solution until uniform to obtain a TiO2 precursor solution, adjusting the pH value of the TiO2 precursor solution to 1.5-2.5, vertically suspending a substrate and immersing the substrate in the TiO2 precursor solution, reacting the substrate at 50-80° C. for 3-9 hours under a sealed condition, taking out the substrate, rinsing, and drying the substrate to obtain a TiO2 thin film on the substrate, wherein the ratio of boric acid in the boric acid aqueous solution to ammonium fluorotitanate in the ammonium fluorotitanate aqueous solution is (0.05-0.17):(0.05-0.18) by mass;
[0011] In S1, the ratio of boric acid in the boric acid aqueous solution to ammonium fluorotitanate in the ammonium fluorotitanate aqueous solution is (0.0556-0.1669):(0.0594-0.1781) in parts by mass.
[0012] In S1, the concentration of boric acid in the boric acid aqueous solution is 1.8 to 5.6 mg / mL, and the concentration of ammonium fluorotitanate in the ammonium fluorotitanate aqueous solution is 1.9 to 6 mg / mL;
[0013] In S1, the drying temperature is 60-80°C, and the drying time is 1-2 hours.
[0014] In S1, the washing is carried out using anhydrous ethanol and water.
[0015] In S1, the pH value is achieved by dropwise adding HCl with a concentration of 9 to 12 mol / L.
[0016] In S1, during the reaction, at least 60-80% of the length of the substrate is immersed in the TiO2 precursor solution.
[0017] S2, thioacetamide and anhydrous ethanol are mixed, and stirred at 60-90° C. until clarified to obtain a mixed solution, and stannous chloride is mixed with the mixed solution, and stirred at 60-90° C. until black to obtain a SnS precursor solution, 60-80% of the length of the surface-treated TiO2 film is vertically suspended and immersed in the SnS precursor solution, and allowed to react at 60-90° C. for 30-60 min under sealed conditions, and then rinsed and dried to obtain a SnS / TiO2 film, wherein the ratio of the mass fraction of thioacetamide, the volume fraction of anhydrous ethanol and the mass fraction of stannous chloride is (2.2539-4.5078): (100-200):
[0018] (1.8926~3.7852), the unit of mass fraction is g, and the unit of volume fraction is mL, wherein the method for surface treatment of the TiO2 film is: vertically suspending the TiO2 film in boiling anhydrous ethanol for 10~20 minutes.
[0019] In S2, the drying temperature is 60-80°C, and the drying time is 3-5 hours.
[0020] A PEC type self-powered light detection performance testing device comprises: a photoanode immersed in an electrolyte, a counter electrode and a reference electrode, wherein the photoanode is a substrate obtained by a method for preparing a SnS / TiO2 film and a SnS / TiO2 film covered thereon, and the substrate is a conductive substrate.
[0021] In the above technical solution, the electrolyte is a mixture of a solvent and a solute, the solute is Na2SO4, and the solvent is water.
[0022] In the above technical solution, the electrolyte is neutral.
[0023] In the above technical solution, the conductive substrate is FTO conductive glass or ITO conductive glass.
[0024] In the above technical solution, the concentration of Na2SO4 in the electrolyte is 0.1-1.0M.
[0025] The beneficial effects of the present invention are:
[0026] 1. In the SnS / TiO2 thin film preparation method of the present invention, the TiO2 thin film is deposited by liquid phase deposition, and the SnS thin film is deposited by chemical bath deposition, and the TiO2 thin film (spherical particles) and the SnS thin film (sheet-like stacked particles) are deposited on the substrate in sequence;
[0027] 2. The SnS / TiO2 film is coated on the substrate as a photoanode, a reference electrode and a counter electrode to form a three-electrode system, which is used in PEC-type self-powered light detection. The built-in electric field of the SnS / TiO2 film and the interface barrier between the photoanode and the electrolyte help to achieve the separation and migration of photogenerated electrons and holes under zero bias, thereby achieving the purpose of PEC-type self-powered light detection;
[0028] 3. Compared with single material film, the SnS / TiO2 film assembled PEC type self-powered light detection performance test device has a 9-fold increase in photocurrent density under ultraviolet light, and the response time τ rise It is shortened from 1230ms to 40ms, and the light response range is widened to the visible region, which can realize dual-wavelength (ultraviolet-visible light) underwater optical communication applications. The SnS / TiO2 film improves the light response characteristics of a single material film and widens the light response range of the PEC-type self-powered light detection performance test device. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the preparation process of SnS / TiO2 thin film;
[0030] Figure 2 (a) is a scanning electron micrograph of the surface of the TiO2 film (TiO2 film before surface treatment), (b) is a scanning electron micrograph of the cross section of the TiO2 film, (c) is a scanning electron micrograph of the surface of the SnS / TiO2 film, and (d) is a scanning electron micrograph of the cross section of the SnS / TiO2 film;
[0031] Figure 3 It is a structural schematic diagram of a PEC type self-powered optical detection performance test device;
[0032] Figure 4 (a) is the It curve obtained by assembling a PEC type self-powered light detection performance test device using TiO2 thin film, (b) is the It curve obtained by assembling a PEC type self-powered light detection performance test device using SnS / TiO2 thin film, (c) is the variation law of the photocurrent density and responsivity obtained by assembling a PEC type self-powered light detection performance test device using TiO2 thin film, (d) is the variation law of the photocurrent density and responsivity obtained by assembling a PEC type self-powered light detection performance test device using SnS / TiO2 thin film.
[0033] Figure 5 (a) is the response time of the PEC type self-powered light detection performance test device assembled by TiO2 thin film under 365nm illumination, and (b) is the response time of the PEC type self-powered light detection performance test device assembled by SnS / TiO2 thin film under 365nm illumination. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0035] In the following embodiments, the substrate pretreatment method is as follows: wipe with absorbent cotton and detergent to remove surface pollutants, rinse with deionized water, then use acetone, isopropanol and anhydrous ethanol for ultrasonic treatment for 10 minutes each, dry in a drying oven at 80°C for 30 minutes, and finally perform UV treatment for 15 minutes to improve the hydrophilicity of the substrate.
[0036] In the following examples, the boric acid aqueous solution is a mixture of boric acid and ultrapure water, and the ammonium fluorotitanate aqueous solution is a mixture of ammonium fluorotitanate and ultrapure water.
[0037] The raw materials and their manufacturers' information involved in the following examples are as follows:
[0038] Ammonium fluorotitanate (analytical grade, Shanghai Aladdin Reagent Company); boric acid (analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.); anhydrous ethanol (99.7%, Tianjin Fuchen Chemical Reagent Co., Ltd.); stannous chloride (analytical grade, Tianjin Chemical Reagent Wholesale Company); thioacetamide (99.99%, Shanghai Aladdin Reagent Company); sodium sulfate (analytical grade, Tianjin Fuchen Chemical Reagent Co., Ltd.).
[0039] The instruments and their model information involved in the following embodiments are as follows:
[0040] Constant temperature heating water bath with magnetic stirrer (DF-101SZT2L); electrochemical workstation (Autolab PGSTAT128N); field emission scanning electron microscope (Hitachi S-8010).
[0041] Example 1
[0042] A method for preparing a SnS / TiO2 thin film, such as Figure 1 As shown, the following steps are included:
[0043] S1, mixing a boric acid aqueous solution and an ammonium fluorotitanate aqueous solution uniformly to obtain a TiO2 precursor solution, adjusting the pH value of the TiO2 precursor solution to 2 by dropping 12 mol / L HCl, wrapping the pretreated substrate with polytetrafluoroethylene tape, hanging it vertically and immersing it in the TiO2 precursor solution (80% of the length of the substrate is immersed in the TiO2 precursor solution), heating and reacting it in a 75°C water bath under sealed conditions for 6 hours, taking out the substrate, rinsing it with anhydrous ethanol and deionized water, and drying it in an oven at 60°C for 1 hour to obtain a TiO2 film on the substrate, wherein, by mass, the ratio of boric acid in the boric acid aqueous solution to ammonium fluorotitanate in the ammonium fluorotitanate aqueous solution is 0.1669:0.1781, the concentration of boric acid in the boric acid aqueous solution is 5.56 mg / mL, and the concentration of ammonium fluorotitanate in the ammonium fluorotitanate aqueous solution is 5.94 mg / mL;
[0044] S2, heat 100mL of anhydrous ethanol to 80°C in a water bath, mix thioacetamide and anhydrous ethanol in a water bath, stir at 80°C at 500rpm for 10min until clarified to obtain a mixed solution, then mix stannous chloride with the mixed solution, stir at 80°C until black, to obtain a SnS precursor solution, vertically hang the surface-treated substrate and the TiO2 film thereon (with an immersion length ratio of 80%) and immerse them in the SnS precursor solution, let it stand at 80°C for 30min under sealed conditions for reaction, take it out after the reaction, and rinse it alternately with anhydrous ethanol and deionized water To remove impurities, vacuum dry at 60°C for 4h to obtain SnS / TiO2 film, wherein the ratio of the mass fraction of thioacetamide, the volume fraction of anhydrous ethanol and the mass fraction of stannous chloride is 2.2539:100:1.8926, the unit of mass fraction is g, the unit of volume fraction is mL, and the method for surface treatment of TiO2 film is as follows: first, keep the reaction container filled with anhydrous ethanol in a water bath at 80°C for 30min, then vertically hang the substrate and the TiO2 film thereon in 100ml of boiling anhydrous ethanol, and continue heating at 80°C for 10min.
[0045] Figure 2 (a) is a scanning electron microscope image of the TiO2 film surface before surface treatment. It can be seen that the TiO2 film is composed of uniform spherical particles. Figure 2 (b) is a scanning electron microscope image of the cross section of the TiO2 film before surface treatment. It can be seen that the thickness of the TiO2 film (particles) is 0.41 μm.
[0046] like Figure 2 As shown in (c), the scanning electron microscopy of the SnS / TiO2 film surface shows that the SnS film is a sheet-like stacked particle film. Figure 2(d) is a scanning electron micrograph of the cross section of the SnS / TiO2 film. SnS particles are interspersed in the TiO2 film and are tightly connected to it to form a SnS / TiO2 film (composite film) with a thickness of 1.2 μm.
[0047] Comparative Example 1
[0048] A TiO2 film, which is the same as the TiO2 film obtained in S1 in Example 1.
[0049] A PEC type self-powered optical detection performance test device, such as Figure 3 As shown, a three-electrode system is used, which specifically includes: a photoanode immersed in an electrolyte, a counter electrode and a reference electrode. The photoanode is a substrate and a thin film (size 1×1 cm) covered thereon. 2 ), the substrate is a conductive substrate (ITO conductive glass), the film is the SnS / TiO2 film prepared in Example 1 or the TiO2 film of Comparative Example 1, the counter electrode is a platinum wire electrode, and the reference electrode is Ag / AgCl. In a quartz electrolytic cell, the photoanode, the counter electrode and the reference electrode are immersed in a neutral electrolyte and placed in dark conditions. An optical window is formed on the side wall of the quartz electrolytic cell, and a light source is installed on the optical window to provide light to the photoanode. The photoanode, the counter electrode and the reference electrode are respectively connected to an electrochemical workstation to obtain a PEC type self-powered light detection performance test device, wherein the electrolyte is a mixture of a solvent and a solute, and the concentration of the solute in the electrolyte is 0.1 to 1.0 M. In this embodiment, the concentration of the solute in the electrolyte is 0.5 M, the solvent is deionized water, and the solute is Na2SO4.
[0050] Figure 4 (a) and (c) are the PEC type self-powered light detection performance test device assembled from the TiO2 film obtained in Comparative Example 1 and the SnS / TiO2 film prepared in Example 1 at different wavelengths, without external bias, and with a light intensity of 2mW / cm 2 , It curve obtained under periodic switching of the light source, where photocurrent density = light current - dark current, responsivity = photocurrent density / incident light power density, according to the calculation formula, we get Figure 4 (b) and (d), Figure 4 (b) shows the variation of the photocurrent density and responsivity of the TiO2 film with the wavelength of light. Figure 4 (d) shows the variation of the photocurrent density and responsivity of SnS / TiO2 film with the wavelength of light. Figure 4 Medium photocurrent density I phis the difference between the photocurrent density under illumination and the photocurrent density in the dark state, the responsivity is the photocurrent density / incident light power density, and I is the photocurrent density. The photocurrent density of the PEC-type self-powered light detection performance test device formed by the TiO2 film gradually decreases with the increase of the illumination wavelength, and there is no light response under the illumination of visible light λ>400nm. The photocurrent density of the PEC-type self-powered light detection performance test device of the SnS / TiO2 film also gradually decreases with the increase of the illumination wavelength, and there is still a light response under 420nm visible light, indicating that the introduction of the narrow bandgap SnS film broadens the light response range of the photoanode. In addition, under 365nm illumination, the photocurrent of the PEC-type self-powered light detection performance test device of the TiO2 film is 0.88μA / cm 2 , while the photocurrent density of the SnS / TiO2 film PEC self-powered light detection performance test device is 8.56μA / cm 2 , compared with 0.88μA / cm 2 It increased by 9 times, indicating that the built-in electric field formed at the interface of SnS / TiO2 film promotes the separation and migration of photogenerated electrons and holes, thereby improving the photoresponse characteristics of the PEC-type self-powered light detection performance test device.
[0051] Response time is a measure of the speed of light detection signal. The rise time of photocurrent density (τ rise ) and fall time (τ decay ) together reflect the response speed characteristics of the light detection to the incident light signal. rise It indicates the time taken for the photocurrent of the PEC self-powered light detection performance test device to rise from 10% of the maximum value in the steady state to 90% at the moment of light on, τ decay It indicates the time taken for the photocurrent of the PEC type self-powered light detection performance test device to drop from 90% of the maximum value in the stable state to 10% at the moment the light is turned off. Figure 5 is the response time of the PEC type self-powered light detection performance test device of TiO2 film and SnS / TiO2 film under 365nm light, and τ of the PEC type self-powered light detection performance test device of TiO2 film rise and τ decay The τ of the PEC-type self-powered optical detection performance test device of SnS / TiO2 film is 1.23s and 0.40s respectively. rise and τ decay They are 0.04s and 0.10s, respectively, indicating that the PEC-type self-powered photodetection of SnS / TiO2 film has a fast photoresponse time.
[0052] In current optical communication systems, the preparation process of thin films is complex and costly. The present invention utilizes a simple, low-cost, low-temperature preparation method to synthesize SnS / TiO2 thin films, which are covered on a conductive substrate as a photoanode, and realizes self-powered dual-wavelength (ultraviolet-visible) light detection optical communication applications in aqueous electrolytes, and provides a new idea for underwater optical communications and flexible optoelectronic devices.
[0053] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A SnS / TiO2 thin film, characterized in that: include: A TiO2 film and a SnS film covering the TiO2 film, wherein the TiO2 film is composed of granular TiO2, and the SnS film is composed of stacked flaky SnS particles.
2. The method for preparing the SnS / TiO2 thin film according to claim 1, characterized in that: The following steps are involved: S1, mixing a boric acid aqueous solution and an ammonium fluorotitanate aqueous solution until uniform to obtain a TiO2 precursor solution, adjusting the pH value of the TiO2 precursor solution to 1.5-2.5, vertically suspending a substrate and immersing the substrate in the TiO2 precursor solution, reacting the substrate at 50-80° C. for 3-9 hours under a sealed condition, taking out the substrate, rinsing, and drying the substrate to obtain a TiO2 thin film on the substrate, wherein the ratio of boric acid in the boric acid aqueous solution to ammonium fluorotitanate in the ammonium fluorotitanate aqueous solution is (0.05-0.17):(0.05-0.18) by mass; S2, thioacetamide and anhydrous ethanol are mixed, and the mixture is stirred at 60-90°C until it becomes clear to obtain a mixed solution, and stannous chloride is mixed with the mixed solution, and the mixture is stirred at 60-90°C until it becomes black to obtain a SnS precursor solution, and the surface-treated TiO2 film is vertically suspended and immersed in the SnS precursor solution, and the film is allowed to react at 60-90°C under sealed conditions for 30-60 min, and then rinsed and dried to obtain a SnS / TiO2 film, wherein the ratio of the mass fraction of thioacetamide, the volume fraction of anhydrous ethanol and the mass fraction of stannous chloride is (2-5):(100-200):(1.5-4), the unit of the mass fraction is g, and the unit of the volume fraction is mL, and the method for surface treatment of the TiO2 film is: the TiO2 film is vertically suspended in boiling anhydrous ethanol for 10-20 min.
3. The preparation method according to claim 2, characterized in that: In S1, the ratio of boric acid in the boric acid aqueous solution to ammonium fluorotitanate in the ammonium fluorotitanate aqueous solution is (0.0556-0.1669):(0.0594-0.1781) in parts by mass.
4. The preparation method according to claim 3, characterized in that: In S1, the concentration of boric acid in the boric acid aqueous solution is 1.8 to 5.6 mg / mL, and the concentration of ammonium fluorotitanate in the ammonium fluorotitanate aqueous solution is 1.9 to 6 mg / mL.
5. The preparation method according to claim 4, characterized in that: In S1, during the reaction, at least 60 to 80% of the length of the substrate is immersed in the TiO2 precursor solution.
6. The preparation method according to claim 5, characterized in that: In S1, the pH value is achieved by dripping HCl with a concentration of 9 to 12 mol / L, the drying temperature is 60 to 80°C, the drying time is 1 to 2 hours, and the washing is performed using anhydrous ethanol and water.
7. The preparation method according to claim 6, characterized in that: In S2, the drying temperature is 60-80°C, and the drying time is 3-5 hours.
8. A PEC type self-powered optical detection performance test device, characterized in that: include: The photoanode, counter electrode and reference electrode are immersed in the electrolyte. The photoanode is a substrate obtained by the preparation method of SnS / TiO2 film and a SnS / TiO2 film covered thereon. The substrate is a conductive substrate.
9. The PEC type self-powered light detection performance testing device according to claim 8, characterized in that: The electrolyte is a mixture of a solvent and a solute, the solute is Na2SO4, the solvent is water, the concentration of Na2SO4 in the electrolyte is 0.1-1.0M, and the electrolyte is neutral.
10. The PEC type self-powered light detection performance testing device according to claim 9, characterized in that: The conductive substrate is FTO conductive glass or ITO conductive glass.